2019
DOI: 10.1089/hgtb.2019.039
|View full text |Cite
|
Sign up to set email alerts
|

Development of Automated Separation, Expansion, and Quality Control Protocols for Clinical-Scale Manufacturing of Primary Human NK Cells and Alpharetroviral Chimeric Antigen Receptor Engineering

Abstract: In cellular immunotherapies, natural killer (NK) cells often demonstrate potent antitumor effects in high-risk cancer patients. But Good Manufacturing Practice (GMP)-compliant manufacturing of clinical-grade NK cells in high numbers for patient treatment is still a challenge. Therefore, new protocols for isolation and expansion of NK cells are required. In order to attack resistant tumor entities, NK cell killing can be improved by genetic engineering using alpharetroviral vectors that encode for chimeric anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 54 publications
(66 reference statements)
1
39
0
Order By: Relevance
“…The alpharetroviral vector system is based on self-inactivating (SIN) alpharetroviral vectors with a split-packaging design (40). These alpharetroviral vectors were successfully used to genetically modify NK cells (45,53,54) and outperformed lentiviral and gammaretroviral transduction efficiencies of PB-derived NK cells using EGFP encoding vectors (45). Furthermore, due to its more random integration pattern with lower frequency of integrations in or close to gene coding regions, alpharetroviral vectors can be considered to be safer as insertional oncogenesis is less likely to occur (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…The alpharetroviral vector system is based on self-inactivating (SIN) alpharetroviral vectors with a split-packaging design (40). These alpharetroviral vectors were successfully used to genetically modify NK cells (45,53,54) and outperformed lentiviral and gammaretroviral transduction efficiencies of PB-derived NK cells using EGFP encoding vectors (45). Furthermore, due to its more random integration pattern with lower frequency of integrations in or close to gene coding regions, alpharetroviral vectors can be considered to be safer as insertional oncogenesis is less likely to occur (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…This production process normally takes two to three weeks to culture NK cells with certain cytokines (IL-2 or in combination with IL-15 or anti-CD3 mAb) (45). The combination of IL-2 and IL-21 were also utilized to improve NK cells proliferation (46,47). The studies suggested that the combination of IL-2 and IL-21 showed a higher inhibitive effect on proliferation of cancer cells than employing IL-2 alone (46,47).…”
Section: Mass Production Of Nk Cellsmentioning
confidence: 99%
“…A major next wave of NK cell immunotherapy will very likely involve the genetic modification of NK cells to overcome specific inherent weakness or enable NK cells new function. Viral and non‐viral approaches to gene modification of NK cells may find application if the NK cells can be propagated to large numbers after small‐scale genetic engineering …”
Section: Lessons Learned and Continued Controversiesmentioning
confidence: 99%